Search in a Known Pattern - Perry, Motty; Wigderson, Avi (Journal of Political Economy, 1986)
In this paper a market where a buyer (job seeker) is searching in a known order among sellers (e.g., a motorist driving along a road looking for gasoline) is described. Both sellers and buyers are assumed to behave strategically. There are many types of buyers. The sellers know only the distribution of all possible buyers; similarly, buyers have imperfect information about sellers. The analysis is conducted by modeling the market as a game with incomplete information; the equilibrium is characterized. A central feature of the game is that both buyers and sellers rationally update their prior information about each other as the game unfolds sequentially. It is shown that prices need not vary monotonically along the search process.